Environmental innovation, open innovation dynamics and competitive advantage of medium and large-sized firms - Michalis Skordoulis; Stamatios Ntanos; Grigorios L. Kyriakopoulos; Garyfallos Arabatzis; Spyros Galatsidas; Miltiadis Chalikias (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The present research investigates the contribution of environmental innovation to firms' competitive advantage through the case of medium and large-sized firms operating in Greece. Due to the growing trend of environmental innovation in Greece and a consequent increase in the research interest, this paper fills the existing gap in the relevant literature as there is not enough evidence concerning Greek firms' environmental innovation practices. To meet the research goal, a questionnaire was distributed to 892 medium and large-sized firms operating in Greece; 225 questionnaires were finally responded. The data is based on firms' self-assessment concerning environmental innovation and competitive advantage and are analyzed using both descriptive and inductive statistics, including principal components analysis and multiple linear regression. The research results show that the examined firms implement environmental innovation practices at a moderate level. The most common practices of environmental innovation are the implementation of ISO 14001 management systems and the toxic substances usage reduction. The percentage of ISO 14001 implementation is increased compared to the previous years. Furthermore, the regression analysis revealed that the components concerning environmental process innovation and environmental product innovation have a positive impact on the examined firms' competitive capability. The relationship between open innovation and environmental innovation and the contribution of open innovation dynamics are discussed as well.
Keywords: 650; firm performance; competitive advantage; environmental innovation; environmental performance; green entrepreneurship; green innovation; open innovation